2020
DOI: 10.3389/fgene.2020.00124
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Prediction Using Low Density Marker Panels in Aquaculture: Performance Across Species, Traits, and Genotyping Platforms

Abstract: Genomic selection increases the rate of genetic gain in breeding programs, which results in significant cumulative improvements in commercially important traits such as disease resistance. Genomic selection currently relies on collecting genome-wide genotype data accross a large number of individuals, which requires substantial economic investment. However, global aquaculture production predominantly occurs in small and medium sized enterprises for whom this technology can be prohibitively expensive. For genom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
56
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 26 publications
12
56
1
1
Order By: Relevance
“…Adequate sample size for the genotyped and phenotyped population is key to fully assess the efficacy of genomic selection (for example, >1,000 individuals), but the population structure is equally important, as prediction accuracy is very dependent on the proximity of relationships between animals in the training and validation sets 74 . While several thousand genome-wide markers are also required, it is noteworthy that a reduction in SNP density down to only 1,000 or 2,000 SNPs tends to be sufficient to achieve the asymptote of prediction accuracy where these close relationships exist 66,75 . However, the accuracy drops drastically as the relationship between the reference and test populations becomes more distant, as demonstrated in Atlantic salmon 76 and common carp (Cyprinus carpio) 77 ; therefore, routine trait measurement and genotyping are required each generation to retrain the genomic prediction models.…”
Section: [H2] Genomic Selection To Accelerate Trait Improvementmentioning
confidence: 99%
“…Adequate sample size for the genotyped and phenotyped population is key to fully assess the efficacy of genomic selection (for example, >1,000 individuals), but the population structure is equally important, as prediction accuracy is very dependent on the proximity of relationships between animals in the training and validation sets 74 . While several thousand genome-wide markers are also required, it is noteworthy that a reduction in SNP density down to only 1,000 or 2,000 SNPs tends to be sufficient to achieve the asymptote of prediction accuracy where these close relationships exist 66,75 . However, the accuracy drops drastically as the relationship between the reference and test populations becomes more distant, as demonstrated in Atlantic salmon 76 and common carp (Cyprinus carpio) 77 ; therefore, routine trait measurement and genotyping are required each generation to retrain the genomic prediction models.…”
Section: [H2] Genomic Selection To Accelerate Trait Improvementmentioning
confidence: 99%
“…It has been integrated in some aquaculture species, including Atlantic salmon (Ødegård et al 2014 ; Tsai et al 2015 ; Robledo et al 2018b ), Yesso scallop ( Patinopecten yessoensis ) (Dou et al 2016 ), Pacific oyster (Gutierrez et al 2018 ), and coho salmon ( Oncorhynchus kisutch ) (Barría et al 2018 ). Although hundreds of thousands of SNPs are required to conduct GS for livestock animals (Fan et al 2010 ), it appears that a few thousand of SNPs are sufficient to gain high prediction accuracy in aquaculture species where cultured populations often consist of closely related individuals (Zenger et al 2019 ; Kriaridou et al 2020 ). At the population level, we were able to detect 22 K SNP loci using GRAS-Di in our rather small population, and therefore, we expect that GRAS-Di can be applied for GS of aquaculture species.…”
Section: Discussionmentioning
confidence: 99%
“…Fish breeding faces the same problems in this regard since the breeding scheme, the typical farm size and the average individual value are similar to those of pig and chicken. Due to these reasons, only the most affordable approaches (e.g., low density genotyping) can be applied routinely even in high-value fish species (Lillehammer et al, 2013;Kriaridou et al, 2020). Reduction of the density and thus the price of the SNP chip seems to be a key factor for the widespread applicability of GS in aquaculture species.…”
Section: Genomic Selectionmentioning
confidence: 99%
“…The tremendous number of siblings produced from a single spawning can be divided to RP and selection candidates. Huge genomic segments shared between these two closely related populations ensure the reliable genome-wide LD representation by even a low density array (Kriaridou et al, 2020). GS has been applied in Atlantic salmon for growth traits (Tsai et al, 2015), for sea lice resistance (Houston et al, 2014;Tsai et al, 2016); in rainbow trout for bacterial cold water disease resistance (Vallejo et al, 2016(Vallejo et al, , 2017, but examples can be also found among the high-volume species like common carp (Palaiokostas et al, 2018), or channel catfish (Garcia et al, 2018); for reviews see Houston et al (2020) and You et al (2020).…”
Section: Genomic Selectionmentioning
confidence: 99%
See 1 more Smart Citation